Impact of Crop Diversification on Household Food and Nutrition Security in Southern and Central Mali - Douyon, Adama; Worou, Omonlola Nadine; Diama, Agathe; Badolo, Felix; Denou, Richard Kibarou; Touré, Sidi; Sidibé, Amadou; Nebie, Baloua; Tabo, Ramadjita (Frontiers in Sustainable Food Systems, 2022)
Many African countries, including Mali, depend on the production of a single or a limited range of crops for national food security. In Mali, this heavy reliance on a range of basic commodities or staple crops, or even just one, exacerbates multiple risks to agricultural production, rural livelihoods, and nutrition. With this in mind, the smart food campaign was initiated to strengthen the resilience and nutritional situation of households and peasant communities where the diet is mainly cereal-based and remains very undiversified and poor in essential micronutrients. As part of the campaign, our study aims to analyze the impact of agricultural diversification on food consumption and household nutritional security. The analysis uses survey data from 332 individuals randomly selected. Multinomial logistic regression and the Simpson diversity index were used to determine the index and estimate the determinants of crop diversification. The consumption score index weighted by consumption frequency and anthropometric indices (for children) were used to assess the nutritional status of households. The results show four types of strategies of diversification: 7.55% are cereals only, 5.66% combine millet–sorghum–groundnut, 41.51% combine millet–sorghum–groundnut–cowpea, and 45.28% combine millet–sorghum–groundnut–cowpea–maize. The estimation of the regression model shows that socioeconomic factors have a positive influence. With a consumption score index of 34 in the villages and 40.5 in Bamako, based on eight food groups, we find that the quality of food is insufficient in rural areas, but it is acceptable in the urban center of Bamako. Analysis of the nutritional status of children aged 6–48 months reveals that 30% of the surveyed population is in a situation of nutritional insecurity (all forms combined). To help improve crop diversification and the nutritional quality of foods, we suggest, among other things, subsidies and public spending to facilitate access to inputs that allow the acquisition of a wider range of inputs and services, intensification of nutrition awareness, and education programs to maximize the incentive to consume nutritious foods from self-production and market purchases. Finally, we propose to facilitate access to technologies promoting food diversification and improving food and nutritional security, particularly in rural areas.